REFFERRING EXPRESSION AND HOW IT POTRAYS 18 OF INDONESIA TOP TOURIST DESTINATION 2018 - Sari Rejeki (Journal Albion : Journal of English Literature, Language, and Culture, 2020)
This article is interested in analysing the referring expressions of 18 of Indonesia top tourist destinations 2018 and how they portray Indonesia tourism. The primary and secondary data are taken from the official website of Ministry of Tourism. Data are collected using simak method with note taking technique. Data are analysed using identity method. Referring expression theories are adapted from Yule (1996), Kreidler (1998) and Huford and Heasly (2007). The articles in the official website promoting 18 of Indonesia top tourist destination 2018 reveal there are 79 referring expressions. Through the referring expressions, Indonesia is portrayed as having world class tourism and rich in historical background. Referring expressions also explains tourist destinations which are shown as modern and being the center of trade. It informs tourist destinations which are developing and having unique qualities. Superlatives which are found in many referring expressions imply that Indonesia is the best in terms of its tourism.Keywords: referent; referring expression; tourist destination.